Population of the Central Region of Medina: A Geographical Study - Al-harbi, Madawi Salim; Al-Shorbaji, Rawya Mahsoub Nabi (Journal of natural sciences, life and applied sciences, 2021)
In this study, we learned about the purification of the population mass in the central area of ​​the city of AL-Madinah AL-Munawarah the nature of its distribution among the neighborhoods, the demarcation of demographic changes during the period between (2004-2019), and the analysis of demographic, social and economic characteristics of the heads of families, and the identification of the effects of the discrimination and discrimination between the neighborhoods. And the population increase in the central area. To achieve the objectives of the study and answer its arguments; It was relying on the informative data coming from the governmental authorities, in addition to a professional sample of (1423) family head. The method of the sample was followed (Stratified Random). The study used the inductive method, Historical method, and the result of the location analysis based on a group of evoking methods. The results showed that the population size of the central area of ​​the city of AL-Madinah AL-Munawarah tended to increase it at a rate of 74%, and the results of scattering, and the standard degree showed the temporal and spatial variation of store distribution among neighborhoods, and the population density was higher than the general average of the city of AL-Madinah AL-Munawarah The scarcity of population concentration: 15.35% in (2004), and 24.32% in (2019).